Faktor-Faktor yang Berhubungan dengan Keaktifan Ibu Balita dalam Kegiatan Posyandu di Kelurahan Satar Peot Kabupaten Manggarai Timur - Mersiana Meilani Paput; Marselinus Laga Nur; Tanti Rahayu (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Posyandu activities are useful as monitoring the growth and development and nutritional status of toddlers as well as early detection of growth and development disorders and health status of toddlers. This study aims to determine the relationship between knowledge, education, employment, distance from home to posyandu and family support with the activeness of mothers of toddlers in posyandu activities. Research method: Quantitative with a cross-sectional approach. The population of this study was 399 mothers of toddlers in Satar Peot Village, East Manggarai Regency. Sampling used a simple random sampling technique with a sample of 80 respondents. The research instrument used a questionnaire. Univariate analysis used a frequency distribution test and a percentage of each variable. Bivariate analysis used a chi square correlation test. Results: Mothers who are active in posyandu activities are 31 (38.8%), Mothers' knowledge about posyandu is 42 (52.2%), the majority of mothers' education is high as many as 52 (65.0%), Mothers who work are 52 (65.0%), The distance from home to posyandu is more likely to be closer as many as 50 (62.5%), Family support is more likely not to support as many as 54 (67.5%). Knowledge (p value = 0.428), education (p value = 0.170), employment (p value = 0.170), distance from home to posyandu (p value = 0.213) have no relationship with mothers' activeness in posyandu while family support is related to mothers' activeness in posyandu (p volume <0.016).